Pb Content in the Organs of Baung Fish (Hemibagrus mumurus) from the Outlet of the Koto Panjang Reservoir, Riau Province - Ratna Purnama Sari; Budijono Budijono; M.Hasbi M.Hasbi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACTThe Outlet Waters of the Koto Panjang Reservoir get an abundance of water from the Koto Panjang Reservoir.The reservoir is used for fishing, plantation and other activities that have the potential to cause pollution, especially by heavy metals.Heavy metals are very dangerous because they cannot be destroyed by living things.This study aims to determine the heavy metal content of Pb in the organs (gills, kidneys, muscles) of baung fish (Hemibagrus mumurus) at the Outlet of the Koto Panjang Reservoir, Lubang Kolam, Kampar Regency.This research was conducted using a survey method by observing and taking samples of baung fish and water quality parameters (temperature, pH, depth, brightness, DO and CO2) from the Outlet flow of the Koto Panjang Reservoir. The content of heavy metal Pb was analyzed by Atomic Absorption Spectrophotometer at the UPT Construction Materials Laboratory of the PUPR Office of Riau Province.This research was conducted in August-December 2020.The results showed that the average heavy metal content of Pb in the kidneys of baung fish was 0.032 mg/kg, gills was 0.026 mg/kg and muscles were 0.007 mg/kg. It was concluded that the Pb content in baung fish was in accordance with SNI 7387:2009 and the fish was fit for consumption. Keywords: Hemibagrus nemurus,heavy metal, Pb, Koto Panjang Reservoir Outlet